C1 Positivity Constrained Interpolation By Weighted Rational Cubic Triangles - Chua, Hua Siong (2017)
The construction of positivity bivariate 1 C interpolants to scattered data using rational cubic Bézier triangular patches is considered. The interpolating surface is formed piecewise as a convex combination of three rational cubic Bézier triangles. Sufficient 1 C continuity conditions along the common boundary of two adjacent rational cubic Bézier triangles are shown. The sufficient positivity conditions on rational cubic Bézier triangle are derived. The initial values of the Bézier ordinates are determined by the data and the estimated gradient at the data sites while the weights are given the value one.